Prevalence of Conventional Risk Factors in Acute Coronary Syndrome Patients in Eastern Part of Nepal (Journal of Nobel Medical College, 2017)
Background: Smoking, diabetes mellitus, hypertension and dyslipidemia are known as conventional risk factors of coronary artery disease (CAD) and the prevalence of it varies across populations. There is paucity of data in our country about the prevalence of risk factors for acute coronary syndrome (ACS). This study aims to assess the prevalence of these conventional risk factors in patients who were admitted in Nobel medical college, with the diagnosis of ACS.Material & Methods: In this observational study, we enrolled 102 patients diagnosed as ACS with stenosis ≥50% of any epicardial arteries as shown on angiography admitted in Nobel Medical College between September 2015 to March 2017 and evaluate the prevalence of conventional risk factors. In addition, we analyzed the lipid profiles within 24 hour of the event.Results: Mean age of the patients was 59 years. Two third (66.7%) of the patients were male. Left anterior descending artery (43.13%) was the most common culprit lesion followed by RCA in 35.29%. Dyslipidemia was present in 73.5%, hypertension in 46.1%, smoking in 38.2% and diabetes in 37.3%. Prevalence of hypertension, diabetes and dyslipidemia was similar among male and female. Smoking (44.1%vs26.5%) was more common in male (P=